Wyzwania i problemy kreacji społeczeństwa informacyjnego w Polsce - Koćwin, Lesław (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2019)
The purpose of the article was to discuss issues related to the information society in Poland. It presents features of the information society and knowledge-based economy as well as the main stages of development of such a society. Based on findings of research conducted author provides an analysis of the development of information society in Poland in comparison with other countries. Problems related to defining a society based on the third wave economy were also included. The consequences of ICT are multidimensional in character, affecting the economic, political and social aspects of life. The analysis of sources: legal acts, statistical data of the Central Statistical Office, Eurostat, CBOS and literature on the subject of studies was used as a research method.
Keywords: ICT; information society